Coastal and Island Public Health Relationship between Environmental Characteristics and Disease Endemicity in Big Island - Puteri Humaerah; Nursafitri Anjani (Journal La Lifesci, 2021)
The purpose of the study to determine the relationship between coastel and island public health and environmental characteristics. The island has a number of health issues that might lead to an endemic sickness. Disease that is endemic to a certain location or population is known as a pandemic. People in poor nations are more vulnerable to the effects of endemic illnesses. Environmental biodiversity and area geography and biological mosquitoes and reservoirs factors, as well as response behavior and attitudes, all play a role in breaking the transmission cycle